Glucose level determination in single cells in their satiety and starvation states using an enzymatic functional glass nanopore. Issue 40 (14th April 2020) - Wang, Dandan; Qi, Guohua; Zhou, Ya; Li, Haijuan; Zhang, Ying; Xu, Chen; Hu, Ping; Jin, Yongdong
Abstract : Enzymatic functional glass nanopipettes containing glucose oxidase (GOx) and cytochrome c (Cyt c ) were developed for detecting glucose in single cells. Abstract : A cytochrome c (Cyt c )-modified glass nanopore sensing platform was constructed to sensitively detect glucose in single cells based on changes in the ionic current rectification (ICR) of the system. A difference in glucose content between single H8 and HeLa cells in their satiety or starvation states was clearly able to be detected using this method.